Impact of Factor V Leiden Polymorphism in Patients with PCOS - Veselin Penkov; Katya Kovacheva; Georgi Golemanov; Galia Georgieva; Peter Ivanov; Regina Komsa-Penkova (Journal of Biomedical & Clinical Research, 2019)
The present study aimed to evaluate the impact of factor V Leiden (FVL) polymorphism within the reproductive problems encountered by patients with polycystic ovary syndrome (PCOS). A total of 92 female patients with PCOS and 101 healthy controls were included in the study. Clinical and laboratory parameters were examined. The full history of each patient was taken. Single nucleotide polymorphism rs6025 in F5 was genotyped in PCOS patients and compared to the genotype frequency of the healthy controls. The data were analysed for correlation with infertility and pregnancy loss in PCOS patients. The prevalence of FVL polymorphism was higher, however not significantly, in PCOS patients compared to that of the control group (respectively OR=2.238, 95 % CI 0.777±6.449, p=0.104). The carriers of FVL polymorphism showed a higher rate of primary infertility (30.0% versus 12.5%, OR=3.143, 9 % CI 0.686±14.388, p=0.047) and their total reproductive failure rate was higher (60.5% versus 47.2%, OR=1.819, 95% CI 0.632±9.259, p=0.117). Carriage of FVL polymorphism in PCOS patients is associated with primary infertility and a presumed cause of the further investigations needed to understand the impact of FVL on PCOS. Carriage of FVL polymorphism in PCOS patients is associated with a higher rate of primary infertility, which draws attention to the role of this factor in the aetiology of the PCOS-related subfertility. Further investigations are needed to understand the impact of FVL on PCOS.